2018
DOI: 10.18521/ktd.368570
|View full text |Cite
|
Sign up to set email alerts
|

Palyatif Bakım Hastalarında Klinik Özellikler ve Prognostik Faktörler

Abstract: Bir palyatif bakım merkezinde yatan hastaların klinik özelliklerini incelemek ve uzun yatış süresi, hastaneden taburculuk durumu ile ilişkili faktörleri araştırmaktır. Gereç ve Yöntem: Kesitsel ve retrospektif bir çalışmadır. Palyatif bakım merkezinde 1 Ağustos 2015-30 Temmuz 2017 tarihleri arasında yatan hastaların dosyaları incelendi. Tüm hastaların demografik özellikleri, komorbid durumları, ilaç sayıları, yatış şikayetleri, ilk yatışındaki nutrisyon, bası yarası ve ağrı durumları değerlendirildi. Hastaları… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 13 publications
3
12
1
7
Order By: Relevance
“…Similar to a previous study from Turkey, more than 80% of the patients we evaluated were immobile on admission [21]. The likelihood of prolonged LOS in individuals with mobilization limitation was 2.3 times higher in the medium stay or long stay tertiles than the short LOS tertile.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar to a previous study from Turkey, more than 80% of the patients we evaluated were immobile on admission [21]. The likelihood of prolonged LOS in individuals with mobilization limitation was 2.3 times higher in the medium stay or long stay tertiles than the short LOS tertile.…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, we identified potential indicators of prolonged LOS that can be assessed on admission to the PCU. Our participants represented a typical PCU because of the similarities in average age, gender distribution, proportions of patients with major comorbidities, and median LOS with some previous national [21,22,23] and international [24,10] reports.…”
Section: Discussionmentioning
confidence: 99%
“…Palliative care centers have started to be established in inpatient health facilities within the scope of the "Directive About the Application Procedures and Principles of Palliative Care" which came into force in 2015. In these centers, patients with multiple chronic problems and end-stage cancer patients are followed and receive treatment [5].…”
Section: Introductionmentioning
confidence: 99%
“…21 PB'de bası yarası, beslenme sorunları ve ek hastalıkların varlığı, hastaların yatış süresini uzatarak taburculuk oranını azaltmaktadır. 23 Mortalite oranının yüksek oranda görüldüğü, uzun süreli yatışların olduğu ve tedaviye cevabın çok iyi alınamadığı son dönem bakım hastalarının takip edildiği PB ünitelerinde çalışan sağlık personeli tükenmişlik gibi ruhsal sorunlar yaşayabilmektedir. 24 Çalışmamızda ise çalışanların %87,5'i PB'de sürekli kayıpla karşılaştıkları için tükenmişlik yaşamalarının kaçınılmaz olduğunu belirtmişlerdir.…”
unclassified
“…Türkiye'de çoğu kurumda aktif bir PB poliklinik hizmeti verilmemektedir. 23,27 Mevcut çalışmada ise çalışanların yarısı "PB poliklinik hizmeti verilmelidir." fikrine katılmıştır.…”
unclassified